2018
DOI: 10.1101/388165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanding Parkinson’s disease genetics: novel risk loci, genomic context, causal insights and heritable risk

Abstract: We performed the largest genome-wide association study of PD to date, involving the analysis of 7.8M SNPs in 37.7K cases, 18.6K UK Biobank proxy-cases, and 1.4M controls. We identified 90 independent genome-wide significant signals across 78 loci, including 38 independent risk signals in 37 novel loci. These variants explained 26-36% of the heritable risk of PD. Tests of causality within a Mendelian randomization framework identified putatively causal genes for 70 risk signals. Tissue expression enrichment ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
269
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 146 publications
(288 citation statements)
references
References 38 publications
(29 reference statements)
7
269
3
Order By: Relevance
“…Clinical and demographic characteristics of the cohorts under study are shown in Supporting Information Table S1. Additional details of these cohorts can be found in Nalls and colleagues …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Clinical and demographic characteristics of the cohorts under study are shown in Supporting Information Table S1. Additional details of these cohorts can be found in Nalls and colleagues …”
Section: Methodsmentioning
confidence: 99%
“…Quality‐control (QC) procedures in the IPDGC GWAS data set have been previously described elsewhere . In brief, samples with call rates <95% and whose genetically determined sex from X chromosome heterogeneity did not match that from clinical data were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations